Comparison of Drug Availability in the Inner Ear After Oral, Transtympanic, and Combined Administration - Li, Yang; Kanzaki, Sho; Shibata, Shinsuke; Nakamura, Masaya; Ozaki, Masahiro; Okano, Hideyuki; Ogawa, Kaoru (Frontiers in Neurology, 2021)
Oral administration (OR), transtympanic administration (TT), and combined therapy (CT) are common treatments for idiopathic sudden sensorineural hearing loss. However, these therapeutic modalities remain controversial, and a limited number of laboratory studies on drug delivery into the inner ear serve as the basis of these clinical administration routes. In the present study, we used a new in vivo imaging system to compare the pharmacokinetics of oral route (OR), TT, and CT in the inner ear of transgenic GFAP-Luc mice. Bioluminescence signals were observed in the inner ear 15.8 ± 7.4 min after OR administration. However, these times were significantly reduced in the TT group (1.6 ± 2.8 min) and the CT group (2.5 ± 2.7 min). There were no significant differences among these groups regarding the Tmax (time-to-peak) and T1/2 (biological half-life) of D-luciferin. The peak photon and total photon counts for the OR group mice were significantly different from those in the TT and CT groups. Simultaneously, there was no significant difference between the TT and CT groups for these parameters. This study shows that the OR route is less effective than the TT and CT routes.